Fluid mud dynamics in a tide-dominated estuary: A case study from the Yangtze River. (1st January 2022) - Wu, Hao; Wang, Ya Ping; Gao, Shu; Xing, Fei; Tang, Jieping; Chen, Dezhi
Abstract: Fluid mud plays an important role in the maintenance of the estuarine turbidity maximum (ETM) and makes a significant contribution to estuarine sediment transport. A seabed tripod system and a shipboard vertical profile were deployed to explore the spatial-temporal variation and mechanism of fluid mud in the ETM of the Yangtze Estuary. The near-bed suspended sediment concentration (SSC) measured by OBS and ABS exceeded 50 kg/m 3, confirming the existence of fluid mud. The fluid mud layer varied frequently in thickness during spring and intermediate tides, with a maximum of up to 0.6 m, but maintained stability during neap tides. The thickness rose rapidly during the larger ebb tide in semidiurnal tidal cycles of intermediate tides when the gradient Richardson number ( Ri ) increased to exceed the critical value of 0.25, and the velocity at 0.2 mab was in the range of 0.5–0.8 m/s. The fluid mud layer transported more than twice as much sediment as the low-concentration upper layer did. Waves and intense currents at the flood phase of tide enhanced vertical mixing within the water column, with Ri being reduced to lower than 0.25 and turbulent kinetic energy (TKE) exceeding 0.01 m 2 /s 2, leading to the breakdown of the fluid mud layer. Sediment stratification damps turbulence close to the seabed and leads to gradual solidification of the bottom fluid mud. Approximately 0.2 m of fluid mud deposit was formed on the seabed within 148 h of the observation period. Highlights: Tidally-induced resuspension and aggregation cause fluid mud formation. The thickness of fluid mud increased during the ebb tide and decreased during the flood tide. Fluid mud layer transported more than twice as much sediment as the upper low-concentration layer.